Deep convolutional neural network with random field model for lake ice mapping from Sentinel-1 imagery - Zhiguo Ma; Zihao Liu; Jiabin Pu; Linlin Xu; Kui Li; Linglong Wangqu; Rui Wu; Yiyi Ma; Ye Chen; Claude Duguay (International Journal of Remote Sensing, 2021)

Chronic Ethanol Exposure Induces Deleterious Changes in Cardiomyocytes Derived from Human Induced Pluripotent Stem Cells - Rui Liu; Fangxu Sun; Lawrence C. Armand; Ronghu Wu; Chunhui Xu (Stem Cell Reviews and Reports, 2021)

A multi-dosing regimen to enhance the spatial memory of normal rats with α5-containing GABAA receptor negative allosteric modulator L-655,708 - Congcong Yuan; An Gao; Qiang Xu; Beibei Zhang; Rui Xue; Yan Dou; Chunshui Yu (Psychopharmacology, 2021)

Simvastatin Blocks Reinstatement of Cocaine-induced Conditioned Place Preference in Male Mice with Brain Lipidome Remodeling - Wei Xu; Yuman He; Jiamei Zhang; Hongchun Li; Xuemei Wan; Menglu Li; Yonghai Wang; Rui Xu; Haoluo Zhang; Yanping Dai; Haxiaoyu Liu; Linhong Jiang; et al. (Neuroscience Bulletin, 2021)

Fast and efficient correction for population stratification in multi-locus genome-wide association studies - Rui Liu; Min Yuan; Xu Steven Xu; Yaning Yang (Genetica, 2021)

The transcribed ultraconserved element uc.51 promotes the proliferation and metastasis of breast cancer by stabilizing NONO - Xiaoqing Shi; Xiaofeng Huang; Rui Chen; Yan Li; Yinggang Xu; Weiwei Zhang; Qiannan Zhu; Xiaoming Zha; Jue Wang (Clinical & Experimental Metastasis, 2021)

Selenium-Alleviated Testicular Toxicity by Modulating Inflammation, Heat Shock Response, and Autophagy Under Oxidative Stress in Lead-Treated Chickens - Size Wang; Lulu Hou; Min Wang; Rui Feng; Xu Lin; Shifeng Pan; Qian Zhao; He Huang (Biological Trace Element Research, 2021)

Establishment of an immortalized cell line derived from the pupal ovary of Mythimna separata (Lepidoptera: Noctuidae) and identification of the cell source - Yan Tong; Lu-Qiang Cheng; Xuan Li; Xu-Peng Yu; Rui-Hao Shu; Ji-Hong Zhang; Qian Meng; Qi-Lian Qin; Kai Tang; Jian-Xiang Xu; Huan Zhang (Cell and Tissue Research, 2021)

Altered gray matter volume in MRI-negative focal to bilateral tonic–clonic seizures - Honghao Xu; Haitao Zhu; Lei Luo; Rui Zhang (Acta Neurologica Belgica, 2021)

Picraquanines A－C, three new phenolic derivatives from the stems of Picrasma quassioides - Rui Xu; Dongdong Zhang; Fangfang Shu; Zehai Long; Yiming Li; Zhengtao Wang; Li Yang; Rui Wang (Natural Product Research, 2021)

A New Instrumental Array in Sichuan, China, to Monitor Vibrations and Perturbations of the Lithosphere, Atmosphere, and Ionosphere - Chieh-Hung Chen; Yang-Yi Sun; Kai Lin; Chen Zhou; Rui Xu; Haiyin Qing; Yongxin Gao; Tao Chen; Fei Wang; Huaizhong Yu; Peng Han; Chi-Chia Tang; et al. (Surveys in Geophysics, 2021)

Loganin ameliorates depression-like behaviors of mice via modulation of serotoninergic system - Chen-Hao Pan; Cong-Yuan Xia; Yu Yan; Yan Han; Rui Shi; Jun He; Ze-Xing Wang; Yu-Ming Wang; Wei-Ku Zhang; Jie-Kun Xu (Psychopharmacology, 2021)

A drug–biomarker interaction model to predict the key targets of Scutellaria barbata D. Don in adverse-risk acute myeloid leukaemia - Teng Wang; Chun-yi Lyu; Yue-hua Jiang; Xue-yan Dong; Yan Wang; Zong-hong Li; Jin-xin Wang; Rui-rong Xu (Molecular Diversity, 2021)

Mechanism of environmental factors regulating water consumption of Larix gmelinii forests - Xin Zhang; Qiuliang Zhang; Zhihong Xu; Rui Wang; Yanan Jian; Jingfu Yang; Changlei Sun; Jiafu Wang (Journal of Soils and Sediments, 2021)

Structure and variation of root-associated bacterial communities of Cyperus rotundus L. in the contaminated soils around Pb/Zn mine sites - Pin Gao; Benru Song; Rui Xu; Xiaoxu Sun; Hanzhi Lin; Fuqing Xu; Baoqin Li; Weimin Sun (Environmental Science and Pollution Research, 2021)

Slope system stability reliability analysis with multi-parameters using generalized probability density evolution method - Dezhi Zai; Rui Pang; Bin Xu; Qunying Fan; Mingyuan Jing (Bulletin of Engineering Geology and the Environment, 2021)

The TCP transcription factor PeTCP10 modulates salt tolerance in transgenic Arabidopsis - Yuzeng Xu; Huanlong Liu; Yameng Gao; Rui Xiong; Min Wu; Kaimei Zhang; Yan Xiang (Plant Cell Reports, 2021)

Clarification of the etiology of peach bacteria leaf shot hole caused by Pantoea spp. in Henan Province, China, based on morphological characteristics and multi-locus sequences analysis - Rui Zang; Lu-lu Song; Chao Xu; Xin-ming Yin; Zhan-xiang Qiao; Yue-hua Geng; Meng Zhang (European Journal of Plant Pathology, 2021)

lncRNA SNHG16 Mediates Cell Proliferation and Apoptosis in Cholangiocarcinoma by Directly Targeting miR-146a-5p/GATA6 Axis - Tao Wu; Ming-Sheng Lei; Xu-Zhao Gao; Ting-Gang Xiong; Kang Yang; Qian Gong; Rui Tang; Yue-Peng Tian; Xiao-Hua Fu (Biochemical Genetics, 2021)

Correction to: Automatic calculating grain size of gravels based on micro-resistivity image of well - Donghui Li; Rui Yuan; Zhenfeng Ding; Rui Xu (Arabian Journal of Geosciences, 2021)

Microseismic source location method based on a velocity model database and statistical analysis - Bing-Rui Chen; Tao Li; Xin-Hao Zhu; Fan-Bo Wei; Xu Wang; Ming-Xing Xie (Arabian Journal of Geosciences, 2021)

Axisymmetric large strain consolidation by vertical drains considering well resistance under vacuum pressure - Yupeng Cao; Rui Zhang; Guizhong Xu; Jianwen Xu (Arabian Journal of Geosciences, 2021)

Circular RNA circ-CHI3L1.2 modulates cisplatin resistance of osteosarcoma cells via the miR-340-5p/LPAATβ axis - Zehua Zhang; Qiang Zhou; Fei Luo; Rui Zhou; Jianzhong Xu; Jun Xiao; Fei Dai; Lei Song (Human Cell, 2021)

High-throughput sequencing reveals the spatial distribution variability of microbial community in coastal waters in Shenzhen - Rui Zhang; Yu Liu; Xianfeng Zhao; Zhihui Zhao; Honglian Zhang; Xiaoping Huang; Weiqing Xu; Yuchun Shen; Wensheng Lan (Ecotoxicology, 2021)

Evaluation of Brain Network Properties in Patients with MRI-Negative Temporal Lobe Epilepsy: An MEG Study - Yuejun Li; Haitao Zhu; Qiqi Chen; Lu Yang; Xincai Bao; Fangqing Chen; Haiyan Ma; Honghao Xu; Lei Luo; Rui Zhang (Brain Topography, 2021)

Automatic calculating grain size of gravels based on micro-resistivity image of well - Donghui Li; Rui Yuan; Zhenfeng Ding; Rui Xu (Arabian Journal of Geosciences, 2021)

Dynamic simulation of tropical coral reef ecosystem being disturbed by multiple situations - Geng Wang; Rui Dong; Huimin Xu; Dewen Ding (Acta Oceanologica Sinica, 2021)

Remote sensing image segmentation based on the fuzzy deep convolutional neural network - Tianyu Zhao; Jindong Xu; Rui Chen; Xiangyue Ma (International Journal of Remote Sensing, 2021)

TREM-1 Exacerbates Neuroinflammatory Injury via NLRP3 Inflammasome-Mediated Pyroptosis in Experimental Subarachnoid Hemorrhage - Pengfei Xu; Ye Hong; Yi Xie; Kang Yuan; Juanji Li; Rui Sun; Xiaohao Zhang; Xiaolei Shi; Rongrong Li; Jiaonan Wu; Xinfeng Liu; Wei Hu; et al. (Translational Stroke Research, 2021)

The mTOR/NF-κB Pathway Mediates Neuroinflammation and Synaptic Plasticity in Diabetic Encephalopathy - Ting Xu; Jiao Liu; Xin-rui Li; Yinghua Yu; Xuan Luo; Xian Zheng; Yuan Cheng; Pei-quan Yu; Yi Liu (Molecular Neurobiology, 2021)

Construction and application of easy-to-detect cyanobacteria with vp28 gene - Min-Min Zhuang; Wen Peng; Yang Xu; Xiao-Hui Jia; Ding-Ji Shi; Pei-Min He; Rui Jia (Journal of Applied Phycology, 2021)

Exosomal miR-193b-5p as a regulator of LPS-induced inflammation in dairy cow mammary epithelial cells - Haotian Xu; Tianqi Zhang; Xuequan Hu; Yingying Xie; Rui Wu; Shuai Lian; Jianfa Wang (In Vitro Cellular & Developmental Biology - Animal, 2021)

Temperature and Moisture Modulate the Contribution of Soil Fauna to Litter Decomposition via Different Pathways - Bo Tan; Rui Yin; Jian Zhang; Zhenfeng Xu; Yang Liu; Shuqin He; Li Zhang; Han Li; Lixia Wang; Sining Liu; Chengming You; Changhui Peng (Ecosystems, 2021)

MicroRNA-363-3p Inhibits the Expression of Renal Fibrosis Markers in TGF-β1-Treated HK-2 Cells by Targeting TGF-β2 - Xiangnan Dong; Yang Li; Rui Cao; Honglan Xu (Biochemical Genetics, 2021)

Seasonal variations of water quality response to land use metrics at multi-spatial scales in the Yangtze River basin - Jiahui Xu; Rui Liu; Maofei Ni; Jing Zhang; Qin Ji; Zuolin Xiao (Environmental Science and Pollution Research, 2021)

Serum Iron and Ferritin Levels Are Correlated with Complement C3 - Shuang Wen; Yeqin Sha; Yinling Li; Zhilian Rui; Chenhong Si; Yuning Zhou; Fengfeng Yan; Bicheng Wang; Jingming Hu; Xu Han; Dongyan Shi (Biological Trace Element Research, 2021)

Foetidibacter luteolus gen. nov., sp. nov., isolated from the rhizosphere of Salvia miltiorrhiza - Qian Pu; Guo-hong Zeng; Gui-wei Wang; Ling-er Lu; Ang Li; Xu-rui Cheng; Xue-ying Wang; Ou Li; Cong Sun; Xiu-fang Hu (Archives of Microbiology, 2021)

Conservation and divergence of the TaSOS1 gene family in salt stress response in wheat (Triticum aestivum L.) - Wei Jiang; Rui Pan; Sebastian Buitrago; Chu Wu; Salah Fatouh Abou-Elwafa; Yanhao Xu; Wenying Zhang (Physiology and Molecular Biology of Plants, 2021)

Systematic analysis of differentially expressed ZmMYB genes related to drought stress in maize - Peng-Yu Zhang; Xiao Qiu; Jia-Xu Fu; Guo-Rui Wang; Li Wei; Tong-Chao Wang (Physiology and Molecular Biology of Plants, 2021)

A New Approach to Embed Complex Fracture Network in Tight Oil Reservoir and Well Productivity Analysis - Jiaxiang Xu; Lifeng Yang; Zhe Liu; Yunhong Ding; Rui Gao; Zhen Wang; Shaoyuan Mo (Natural Resources Research, 2021)

Effects of Tobacco Stem-Derived Biochar on Soil Properties and Bacterial Community Structure under Continuous Cropping of Bletilla striata - Linyan Zhao; Huilin Guan; Rui Wang; Haoji Wang; Zecheng Li; Wei Li; Ping Xiang; Wumei Xu (Journal of Soil Science and Plant Nutrition, 2021)

Effects of Diversified Cropping Sequences and Tillage Practices on Soil Organic Carbon, Nitrogen, and Associated Fractions in the North China Plain - Ahmad Latif Virk; Wen-Sheng Liu; Jia-Rui Niu; Cheng-Tang Xu; Qiu-Yue Liu; Zheng-Rong Kan; Xin Zhao; Hai-Lin Zhang (Journal of Soil Science and Plant Nutrition, 2021)

Classification technology of domestic waste from 2000 to 2019: a bibliometrics-based review - Tianxue Yang; Jiangcheng Xu; Ying Zhao; Tiancheng Gong; Rui Zhao; Mengyang Sun; Beidou Xi (Environmental Science and Pollution Research, 2021)

Generation and identification of endothelial-specific Hrh2 knockout mice - Rui Meng; Wen-Ke Cai; Wen-Mang Xu; Qiang Feng; Ping Wang; Yan-hua Huang; Yu-Xin Fan; Tao Zhou; Qin Yang; Zhi-Ran Li; Gong-Hao He (Transgenic Research, 2021)

Two new dihydroisocoumarins with antimicrobial activities from the fungus Penicillium sp. XR046 collected from Xinren coal area - Guo-Bo Xu; Fei-Yu Yang; Xin-Yu Wu; Rui Li; Meng Zhou; Bing Wang; Xiao-Sheng Yang; Ting-Ting Zhang; Shang-Gao Liao (Natural Product Research, 2021)

Water Qualities and Products Generated in Dechlorination Process Using Ultra-high Lime with Aluminum Method - Jiali Xu; Peng Chen; Chen Dou; Di Yin; GuangYuan Meng; Rui Cheng; Haifeng Liu; Lehua Zhang (Water, Air, & Soil Pollution, 2021)

A functional chromogen gene C from wild rice is involved in a different anthocyanin biosynthesis pathway in indica and japonica - Weihua Qiao; Yanyan Wang; Rui Xu; Ziyi Yang; Yan Sun; Long Su; Lizhen Zhang; Junrui Wang; Jingfen Huang; Xiaoming Zheng; Shijia Liu; Yunlu Tian; et al. (Theoretical and Applied Genetics, 2021)

Correction to: Exploring the Genetic Association of the ABAT Gene with Alzheimer’s Disease - Quanzhen Zheng; Rui Bi; Min Xu; Deng-Feng Zhang; Li-Wen Tan; Ya-Ping Lu; Yong-Gang Yao (Molecular Neurobiology, 2021)

Exploring the Genetic Association of the ABAT Gene with Alzheimer’s Disease - Quanzhen Zheng; Rui Bi; Min Xu; Deng-Feng Zhang; Li-Wen Tan; Ya-Ping Lu; Yong-Gang Yao (Molecular Neurobiology, 2021)

Divergent Projection Patterns Revealed by Reconstruction of Individual Neurons in Orbitofrontal Cortex - Junjun Wang; Pei Sun; Xiaohua Lv; Sen Jin; Anan Li; Jianxia Kuang; Ning Li; Yadong Gang; Rui Guo; Shaoqun Zeng; Fuqiang Xu; Yu-Hui Zhang (Neuroscience Bulletin, 2021)

Microbiological profiles and antimicrobial resistance patterns of pediatric bloodstream pathogens in China, 2016–2018 - Yue Qiu; Junwen Yang; Yiping Chen; Jinhong Yang; Qingxiong Zhu; Chunhui Zhu; Shuangjie Li; Jing Liu; Chaomin Wan; Yu Zhu; Minxia Chen; Yi Xu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Epimutational effects of electronic cigarettes - Rui Yan; Xu-Li Chen; Yan-Ming Xu; Andy T. Y. Lau (Environmental Science and Pollution Research, 2021)

A novel Schiff base cobalt(III) complex induces a synergistic effect on cervical cancer cells by arresting early apoptosis stage - Wen-Hui Liao; Xue-Qing Song; Yan-Jie Kong; Rui-Dan Bao; Fang-Fang Li; Jie Zhou; Qi-Hua Zhao; Jing-Yuan Xu; Ni Xie; Ming-Jin Xie (BioMetals, 2021)

Uncertainty Visualisation of a 3D Geological Geometry Model and Its Application in GIS-Based Mineral Resource Assessment: A Case Study in Huayuan District, Northwestern Hunan Province, China - Nan Li; Cangbai Li; Wenkai Chu; Keyan Xiao; Weihan Tao; Xianglong Song; Rui Cao; Yang Xu; Mingjing Fan (Journal of Earth Science, 2021)

BeiDou-3 broadcast clock estimation by integration of observations of regional tracking stations and inter-satellite links - Yufei Yang; Yuanxi Yang; Xiaogong Hu; Chengpan Tang; Rui Guo; Zhanshi Zhou; Junyi Xu; Junyang Pan; Mudan Su (GPS Solutions, 2021)

TGF-β1-modified MSC-derived exosomal miR-135b attenuates cartilage injury via promoting M2 synovial macrophage polarization by targeting MAPK6 - Rui Wang; Bin Xu (Cell and Tissue Research, 2021)

Polymorphisms in the DC-SIGN gene and their association with the severity of hand, foot, and mouth disease caused by enterovirus 71 - Ya-Ping Li; Mu-Qi Wang; Chen-Rui Liu; Hui-Ling Deng; Yuan Wu; Shuang-Suo Dang; Li-Hong Xu (Archives of Virology, 2021)

Self-Assembled Micelles Improve the Oral Bioavailability of Dihydromyricetin and Anti-Acute Alcoholism Activity - Jing Ye; Sha Bao; Shiying Zhao; Yujing Zhu; Qiao Ren; Rui Li; Xiaohong Xu; Quan Zhang (AAPS PharmSciTech, 2021)

New titanite U–Pb and molybdenite Re–Os ages for a hydrothermal vein-type Cu deposit in the Lanping Basin, Yunnan, SW China: constraints on regional metallogeny and implications for exploration - Juan Li; Lei-Luo Xu; Xian-Wu Bi; Yong-Yong Tang; Xiang-Yuan Sheng; Hai-Jun Yu; Gong Liu; Rui Ma (Mineralium Deposita, 2021)

Heteroaggregation of humic acid with montmorillonite in divalent electrolytes: effects of humic acid content and ionic concentration - Xiaodan Gao; Yingde Xu; Zhongyi Li; Song Li; Rui Tian; Hang Li; Rattan Lal; Lingzhi Liu; Muhammad Farhan Saeed; Jingkuan Wang (Journal of Soils and Sediments, 2021)

Estimates on thermal impact of gas-line and alleviating effect of countermeasures in patchy permafrost of northwestern China - Rui Shi; Xu Wang; Zhi Wen; Desheng Li (Bulletin of Engineering Geology and the Environment, 2021)

Small RNA Sequencing Analysis of Germinating Single-bud Seedcane Sett in Sugarcane - Kai-Chao Wu; Lin Xu; Zhi-Nian Deng; Tian Pang; Rong-Hua Zhang; Yi-Jie Li; Xiao-Yan Liu; Cheng-Feng Huang; Wen-Xian Qin; Jian-Feng Wei; Li-Ping Wei; Yang-Rui Li; et al. (Sugar Tech, 2021)

The role of hydrous mantle-derived magmas in the generation of Late Cretaceous granitoids in the Gangdese batholith: insights from the Shanba and Zongga plutons in the southern Lhasa subterrane, Tibet - Rui-Qiang Wang; Jian-Sheng Qiu; Ding-Jun Wen; Hang Xu (Mineralogy and Petrology, 2021)

Gentianella acuta prevents acute myocardial infarction induced by isoproterenol in rats via inhibition of galectin-3/TLR4/MyD88/NF-кB inflammatory signalling - Jia-Huan Sun; Hong-Xia Yang; Ting-Ting Yao; Yuan Li; Lin Ruan; Geng-Rui Xu; Chuang Zhang; Guo-Xin Guo; Ai-Ying Li (Inflammopharmacology, 2021)

Identification of pepper genes involved in the response to CO2 enrichment using RNA-Seq analysis - Jing Zhang; Rui Bai; Mengya Shang; Xiaoyong Xu; Hongxia Song; Shaowen Zheng; Leiping Hou; Meilan Li; Guoming Xing (Horticulture, Environment, and Biotechnology, 2021)

Renewable energy hybrid subsidy combining input and output subsidies - Zi-rui Chen; Xu Xiao; Pu-yan Nie (Environmental Science and Pollution Research, 2021)

3D slope reliability analysis based on the intelligent response surface methodology - LaiFu Song; Xiang Yu; Bin Xu; Rui Pang; ZeYu Zhang (Bulletin of Engineering Geology and the Environment, 2021)

Formaldehyde-induced hematopoietic stem and progenitor cell toxicity in mouse lung and nose - Yun Zhao; Laura C. Magaña; Haiyan Cui; Jiawei Huang; Cliona M. McHale; Xu Yang; Mark R. Looney; Rui Li; Luoping Zhang (Archives of Toxicology, 2021)

Combining forecast of landslide displacement based on chaos theory - Xunchang Li; Chao Jiang; Rui Xu; Wei Yang; HaoHao Wang; Yu Zou (Arabian Journal of Geosciences, 2021)

Is small hydropower beautiful? Social impacts of river fragmentation in China’s Red River Basin - Tyler Harlan; Rui Xu; Jun He (Ambio, 2021)

An insight into shallow gas hydrates in the Dongsha area, South China Sea - Bin Liu; Jiangxin Chen; Luis M. Pinheiro; Li Yang; Shengxuan Liu; Yongxian Guan; Haibin Song; Nengyou Wu; Huaning Xu; Rui Yang (Acta Oceanologica Sinica, 2021)

Vertical influence of temperature and precipitation on snow cover variability in the Yarlung Zangbo River basin, China - Chunguang Ban; Zongxue Xu; Depeng Zuo; Xiaowan Liu; Rui Zhang; Jing Wang (International Journal of Climatology, 2021)
Seasonal snow cover in mountainous areas is a key source of water for downstream regions. The snow cover area (SCA) in the Northern Hemisphere has significantly decreased during the past decades in response to global warming. Therefore, it is necessary to investigate the primary factors controlling the spatiotemporal variabilities in the SCA in high altitude regions. In this study, based on remote sensing data of SCA, temperature, and precipitation in the Yarlung Zangbo River basin, Pearson's correlation analysis was used to identify the relative importance of temperature and precipitation on the SCA variability with altitude. The results showed that temperature played a more dominant role for the SCA than precipitation at all elevation during the period 2001–2017; three threshold altitudes at high, moderate, and low elevation were identified, and these threshold altitudes are dynamic and vary with time; the threshold altitude at high elevation was 5,925 ± 125 m, below which temperature (precipitation) was negatively (positively) correlated and above which temperature (precipitation) was positively (negatively) correlated with the SCA; the threshold altitude at moderate elevation was 3,200 ± 300 m, below which temperature (precipitation) was positively (negatively) correlated and above which temperature (precipitation) was negatively (positively) correlated with the SCA; the threshold altitude in low elevation regions was 2,100 ± 200 m. This study sheds light on the dominant climatic control factors on the variability in SCA in high altitude regions. These results have major implications for SCA and water resources availability under future climate change.

The substrate‐dependent regulatory effects of the AfeI /R system in Acidithiobacillus ferrooxidans reveals the novel regulation strategy of quorum sensing in acidophiles - Xue‐Yan Gao; Chang‐Ai Fu; Likai Hao; Xiu‐Feng Gu; Rui Wang; Jian‐Qiang Lin; Xiang‐Mei Liu; Xin Pang; Cheng‐Jia Zhang; Jian‐Qun Lin; Lin‐Xu Chen (Environmental Microbiology, 2021)
Summary A LuxI/R‐like quorum sensing (QS) system (AfeI/R) has been reported in the acidophilic and chemoautotrophic Acidithiobacillus spp. However, the function of AfeI/R remains unclear because of the difficulties in the genetic manipulation of these bacteria. Here, we constructed different afeI mutants of the sulfur‐ and iron‐oxidizer A . ferrooxidans , identified the N‐acyl homoserine lactones (acyl‐HSLs) synthesized by AfeI, and determined the regulatory effects of AfeI/R on genes expression, extracellular polymeric substance synthesis, energy metabolism, cell growth and population density of A . ferrooxidans in different energy substrates. Acyl‐HSLs‐mediated distinct regulation strategies were employed to influence bacterial metabolism and cell growth of A . ferrooxidans cultivated in either sulfur or ferrous iron. Based on these findings, an energy‐substrate‐dependent regulation mode of AfeI/R in A . ferrooxidans was illuminated that AfeI/R could produce different types of acyl‐HSLs and employ specific acyl‐HSLs to regulate specific genes in response to different energy substrates. The discovery of the AfeI/R‐mediated substrate‐dependent regulatory mode expands our knowledge on the function of QS system in the chemoautotrophic sulfur‐ and ferrous iron‐oxidizing bacteria, and provides new insights in understanding energy metabolism modulation, population control, bacteria‐driven bioleaching process, and the coevolution between the acidophiles and their acidic habitats.

Elevated atmospheric CO 2 reduces yield‐scaled N 2 O fluxes from subtropical rice systems: Six site‐years field experiments - Zhisheng Yao; Rui Wang; Xunhua Zheng; Baoling Mei; Zaixing Zhou; Baohua Xie; Haibo Dong; Chunyan Liu; Shenghui Han; Zhongjun Xu; Klaus Butterbach‐Bahl; Jianguo Zhu (Global Change Biology, 2021)
Increasing levels of atmospheric CO 2 are expected to enhance crop yields and alter soil greenhouse gas fluxes from rice paddies. While elevated CO 2 ( ) effects on CH 4 emissions from rice paddies have been studied in some detail, little is known how might affect N 2 O fluxes or yield‐scaled emissions. Here, we report on a multi‐site, multi‐year in‐situ FACE (free‐air CO 2 enrichment) study, aiming to determine N 2 O fluxes and crop yields from Chinese subtropical rice systems as affected by . In this study, we tested various N fertilization and residue addition treatments, with rice being grown under either (+200 μmol/mol) or ambient control. Across the six site‐years, rice straw and grain yields under were increased by 9%–40% for treatments fertilized with ≥150 kg N/ha, while seasonal N 2 O emissions were decreased by 23%–73%. Consequently, yield‐scaled N 2 O emissions were significantly lower under . For treatments receiving insufficient fertilization (≤125 kg N/ha), however, no significant effects on N 2 O emissions were observed. The mitigating effect of upon N 2 O emissions is closely associated with plant N uptake and a reduction of soil N availability. Nevertheless, increases in yield‐scaled N 2 O emissions with increasing N surplus suggests that N surplus is a useful indicator for assessing N 2 O emissions from rice paddies. Our findings indicate that with rising atmospheric CO 2 soil N 2 O emissions from rice paddies will decrease, given that the farmers’ N fertilization is usually sufficient for crop growth. The expected decrease in N 2 O emissions was calculated to compensate 24% of the simultaneously observed increase in CH 4 emissions under . This shows that for an agronomic and environmental assessment of effects on rice systems, not only CH 4 emissions, but also N 2 O fluxes and yield‐scaled emissions need to be considered for identifying most climate‐friendly and economically viable options for future rice production.